An exploration of mental strategies of astronauts. - Sprung, Heidi. (University of Ottawa (Canada), 1997)
This study explored mental strategies and perspectives of eight Canadian astronauts within a theoretical framework developed in the field of sport psychology. An Astronaut Interview Guide was developed and the interviews analyzed using accepted qualitative analysis procedures. Astronauts attributed their parents and/or community experiences as young people, with providing supportive yet challenging experiences, and credited that environment with their success in being selected to the astronaut program. Attitudes towards achievement revealed a variety of approaches to achieving goals which overall imply a tremendous dedication, commitment and pleasure in doing things as well as they can be done. The use of mental strategies such as imagery, planning and preparation, and self-evaluation, were described. For some astronauts the preservation of family relationships and being a good parent were revealed as important components of their lives.
Keywords: Education, Educational Psychology.